Ventilação não invasiva com pressão positiva intermitente - experiência de 7 anos - Resende, C (2014)
Introduction: Nasal intermittent positive pressure ventilation (NIPPV) is a non invasive ventilation method that combines the benefits of nasal continuous positive airway pressure (NCPAP) and the cycles of positive pressure. Objectives: Description of the NIPPV experience in a neonatal intensive care unit. Methods: A descriptive study of newborns ventilated with NIPPV, from January 2002 to December 2008. Were considered two groups: the first group had mechanical ventilation before NIPPV, and in the second group the initial method was non-invasive ventilation. These 2 groups were subdivided: Group 1: sub-group A, NIPPV immediately after weaning and sub- group B, NIPPV after mechanical ventilation followed by NCPAP. The group 2 was sub-divided in sub-group C, NIPPV after NCPAP, and sub-group D, NIPPV as the initial mode of ventilation. Results: In group 1 we analysed 79 cycles of ventilation with 89% of success and in group 2 55 cycles, with 69% of success. Newborns in group 1 had a median weight of 925g and gestational age of 27 weeks and the group 2 had 1350g and 30 weeks, respectively. Conclusions: NIPPV was used mainly after conventional ventilation in lighter and immature babies, without relevant complications.